Dampak dan Strategi UMKM (Usaha Mikro Kecil Dan Menengah) Menghadapi The “New Normal” - Endah Marendah Ratnaningtyas (EBBANK, 2020)
Micro, Small and Medium Enterprises (MSMEs) are business activities capable of expanding employment opportunities, providing broad economic services to the community, playing a role in the process of equalization and increasing community income, encouraging economic growth, and playing a role in realizing national stability. The purpose of this study is to determine how MSMEs increase competitiveness in facing the "New Normal". The method used in this study is a qualitative method. The technique of determining the informants was done by purposive sampling. The data analysis process is done by reducing data and presenting the data that has been obtained for later drawing conclusions. The results of this study indicate that MSMEs continue to improve their competitiveness amid the pandemic that is still occurring in Indonesia, although the marketing is still relatively small, but MSME players continue to improve the quality of their products to welcome the "new normal" that will be carried out, so that the wheels the economy started again.